Impacts of ischemic preconditioning in liver resection: systematic review with meta-analysis - de Oliveira, Glauber C. [UNESP]; de Oliveira, Walmar K.; Yoshida, Winston B.; Sobreira, Marcone L. (Wolters Kluwer, 2023)
OBJECTIVE: To assess the beneficial effects of ischemic preconditioning (IPC) in liver resection and evaluate its applicability in clinical practice. SUMMARY BACKGROUND DATA: Liver surgeries are usually associated with intentional transient ischemia for hemostatic control. IPC is a surgical step that intends to reduce the effects of ischemia-reperfusion; however, there is no strong evidence about the real impact of the IPC, and it is necessary to effectively clarify what its effects are. METHODS: Randomized clinical trials were selected, comparing IPC with no preconditioning in patients undergoing liver resection. Data were extracted by three independent researchers according to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, Supplemental Digital Content 1, http://links.lww.com/JS9/A79 . Several outcomes were evaluated, including postoperative peaks of transaminases and bilirubin, mortality, length of hospital stay, length of stay in the ICU, bleeding, and transfusion of blood products, among others. Bias risks were assessed using the Cochrane collaboration tool. RESULTS: Seventeen articles were selected, with a total of 1052 patients. IPC did not change the surgical time of the liver resections while these patients bled less (Mean Difference: -49.97 ml; 95% CI: -86.32 to -13.6; I2 : 64%), needed less blood products [relative risk (RR): 0.71; 95% CI: 0.53-0.96; I2 =0%], and had a lower risk of postoperative ascites (RR: 0.40; 95% CI: 0.17-0.93; I2 =0%). The other outcomes had no statistical differences or could not have their meta-analyses conducted due to high heterogeneity. CONCLUSIONS: IPC is applicable in clinical practice, and it has some beneficial effects. However, there is not enough evidence to encourage its routine use.